Analysis of Consumers' Buying Interest Cifest Walk Tea Tradition Shop Cikarang Selatan Through Promotion, Product Prices and Quality Product - Nur' Aeni; Dadang Heri Kusumah; Primaraga Sumantri Indra Wicaksana (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the effect of promotion, product price and product quality on consumer buying interest in traditional tea shops in Cifest Walk, South Cikarang. The sample in this study were traditional tea shop consumers, as many as 100 respondents. Data collection includes observation, distributing questionnaires and literature study. The type of research used is quantitative. The analytical method used is validity test, reliability test, classical assumption test, multiple linear analysis and hypothesis testing. The results of the t-test research show the t-count value of 2.492 with a significance of 0.014, which means the first hypothesis is accepted and partially shows a positive and significant influence between promotions on consumer buying interest. The product price variable obtained the results of the t-test with a t-count value of 3.050 and a significance value of 0.003 which means that the second hypothesis is accepted and shows a positive and significant influence between product prices on consumer buying interest. The product quality variable obtained t test results with a tcount value of 3.036 and a significant value of 0.003 which means the third hypothesis is accepted and shows a positive and significant influence between product quality on consumer buying interest. And it can be concluded that 32.1% consumer buying interest is influenced by promotion variables, product prices, product quality, while the remaining 67.9% consumer buying interest is influenced by other variables not examined in this study.